Early surgical complications after gastric by-pass: a literature review - ACQUAFRESCA,Pablo A. (2015)
INTRODUCTION: Gastric bypass is today the most frequently performed bariatric procedure,but, despite of it, several complications can occur with varied morbimortality. Probably all bariatric surgeons know these complications, but, as bariatric surgery continues to spread, general surgeon must be familiarized to it and its management. Gastric bypass complications can be divided into two groups: early and late complications, taking into account the two weeks period after the surgery. This paper will focus the early ones. METHOD: Literature review was carried out using Medline/PubMed, Cochrane Library, SciELO, and additional information on institutional sites of interest crossing the headings: gastric bypass AND complications; follow-up studies AND complications; postoperative complications AND anastomosis, Roux-en-Y; obesity AND postoperative complications. Search language was English. RESULTS: There were selected 26 studies that matched the headings. Early complications included: anastomotic or staple line leaks, gastrointestinal bleeding, intestinal obstruction and incorrect Roux limb reconstruction. CONCLUSION: Knowledge on strategies on how to reduce the risk and incidence of complications must be acquired, and every surgeon must be familiar with these complications in order to achieve an earlier recognition and perform the best intervention.